Preclinical evaluation of high-resolution CT, 18F-FDG, and 18F-NaF PET imaging for longitudinal monitoring of atherosclerosis. - Tamboline, Mikayla; Collins, Jeffrey; Jackson, William; Gu, Wenduo; Worssam, Matthew; Cheng, Paul; David, John; Taschereau, Richard; Chatziioannou, Arion F.; Jackson, Simon; Xu, Shili; Ikotun, Oluwatayo F. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Rationale: Detection of atherosclerosis is essential to the management and prevention of life-threatening cardiovascular events. Although non-invasive imaging modalities, such as 18F-sodium fluoride (18F-NaF), 18F-fluorodeoxyglucose (18F-FDG) PET, and CT, visualize distinct hallmarks of atherosclerosis, there has yet to be a singular multi-cohort interrogation of their strengths and limitations. Thus, we focused on identifying the optimal approach for visualizing atherosclerosis at different stages of disease progression. Methods: In this study, 6-week-old, male, ApoE deficient mice (Apoe−/−) were placed on a high cholesterol diet for 12–20 weeks to induce calcific atherosclerotic disease. Age-matched, male, wildtype (WT) C57BL/6 mice fed with regular chow served as the control group. Mice were imaged at 12, 15, 18, and 20 weeks after starting their respective diets. To follow the progression of calcified atherosclerotic lesions, at each time point, in vivo,18F-NaF microPET/CT images were acquired 1 h and 3 h post tracer i.v. injection. In a separate cohort, in vivo 18F-FDG PET/CT images were acquired at 3 and 5 h post tracer i.v. injection to follow inflammation as a result of progressive atherosclerotic lesion formation. High-resolution microCT images were acquired for all mice to visualize aorta calcification. After each imaging session, a subset (n = 3) was euthanized from each group and histological analysis of the aorta was performed to confirm disease progression. Results: In this comparative study, within the same cohort, 18F-NaF PET detected atherosclerotic calcification earlier than microCT. At both 1 and 3 h post-injection (p.i.), calcified lesions were clearly detected by 18F-NaF with a six-fold higher signal in Apoe-/- compared to WT mice. Interestingly, 18F-NaF signal peaked at week 18, whereas aortic CT signal progressively increased with a 13-, 16-, and 29-fold at 15, 18, and 20 weeks, respectively. 18F-FDG arortic accumulation at weeks 12 and 15, were significantly greater in Apoe−/− mice than WT control when images were acquired at 5 h but not at 3 h p.i.. In contrast to histological analysis, at ≥ 16 weeks where inflammation is significantly elevated, 18F-FDG was equivalent in Apoe−/− and WT control mice and significantly reduced with disease progression. Conclusions: Our results show that 18F-NaF PET and 18F-FDG PET are sensitive imaging modalities for the early detection of atherosclerotic lesions. However, both 18F-NaF PET and high-resolution microCT prove to be effective methods for monitoring late-stage and progressive disease.